Rentabilidade, eficiência e risco em cooperativas de crédito e bancos comerciais - Rocha, Isabella de Moura (2023)
In contrast to commercial banks, entities with concentrated ownership, whose predominant focus lies on maximizing profit; Credit cooperatives are socially oriented and collectively managed, with products and services similar to those of a commercial bank. Therefore, the study aims to understand how these entities differ and behave in relation to the variables risk, profitability and efficiency. The study used the Vector Autoregressive Panel Data (PVAR) model, with data from Brazilian credit unions and commercial banks between 2011 and 2021, originating from the Central Bank of Brazil (BCB). The results reveal significant disparities: commercial banks, despite presenting lower profitability and risk than credit unions, demonstrated greater efficiency. The results of the Generalized Impulse Response Functions (GIRF), obtained after estimating the PVAR model, indicated that, for credit cooperatives, a shock to profitability triggers a negative reaction in their own profitability, as well as in commercial banks. A risk shock is associated with increased profitability, suggesting the adaptability of credit unions to higher risks, in contrast to commercial banks. The observed changes in efficiency minimally affected the profitability of credit unions and commercial banks. The influence of the sample on the GIRF results was relevant, as excessively heterogeneous samples of credit unions demonstrated unreliable results in relation to more homogeneous samples. This study contributes to the understanding of the idiosyncrasies of Brazilian credit unions and commercial banks, in addition to providing algorithms for processing data from the BCB.